EVALUATION OF THE PHYSICAL AND ACOUSTICAL COMPETENCES OF VOCATIONAL MUSIC EDUCATION INSTITUTIONS IN TERMS OF THE REQUIREMENTS OF MUSIC EDUCATION - Gök, Murat; Şen, Çağrı (International Online Journal of Education and Teaching, 2022)
The purpose of this research is to evaluate the buildings of higher education institutions in Turkey, where vocational music education is delivered, in terms of physical and acoustical sufficiency. This research is a descriptive study conducted with qualitative method and survey model. The population of the research consists of all of the buildings of the higher education institutions in Turkey, where vocational music education is delivered. Data of the research have been collected through semi-structured interview from instructions who serve in a total of 85 different higher education programs in Turkey, where vocational music education activities are conducted. It was determined in line with the collected data that there are important deficiencies in the buildings of the university institutions in Turkey in terms of both physical and acoustical sufficiency, where vocational music education is delivered. On the other hand, only 14% of the instructors stated that the institutional buildings meet the acoustical needs required by vocational music education. In conclusion, this study tries to make suggestions for the solution of the detected problems in order to create a certain standard in physical and acoustical aspects in the buildings of higher education institutions, where vocational music education is delivered.